Peranan Perjanjian Matunu Tedong Dalam Acara Adat Rambu Solo Di Tana Toraja - Crameraldo Anugerah Putra Openg; Melani Anastasia Wijono; Stefanus Don Rade (Universitas Sains dan Teknologi Komputer, 2024)
Reflecting aspects of local wisdom, such as social values, culture or customs recognized by the local Tana Toraja community. Toraja is an area that has many very unique cultural traditions. One of them is the mantunu tedong ritual, which can be said to be one of the rituals that native Toraja people are certainly proud of. By using normative research methods that focus on research that uses legal sources, statutory regulations, local regional regulations, and legal theory and legal documents relating to wisdom in completing the Matunu Tedong agreement which occurred during the Rambu Solo event in Tana Toraja, South Sulawesi regarding the agreement in the Matunu Tedong event which is one of a series of customs in the Rambu Solo event. In completing this agreement, the Tana Toraja people have methods in accordance with customs and cultural heritage that have existed for a long time.